Treatment with Rhus tripartita extract curtails isoproterenol-elicited cardiotoxicity and oxidative stress in rats. Issue 1 (December 2016) - Shahat, Abdelaaty; Alsaid, Mansour; Rafatullah, Syed; Al-Sohaibani, Mohammed; Parvez, Mohammad; Al-Dosari, Mohammed; Exarchou, Vassiliki; Pieters, Luc
Abstract Background Consumption of plant-derived nutraceuticals and crude drugs in traditional medicine is widely believed to confer beneficial effects in thwarting the progression of cardiovascular diseases.Rhus tripartita (family Anacardiaceae) has been traditionally used to treat a wide range of ailments. Methods In the present study we investigated the protective effects of an alcoholic extract of the stem part ofRhus tripartita male genotype (RTSM) on experimentally induced myocardial injury in rats. To this end, cardiac injury was induced by administration of isoproterenol (ISO) and serum enzyme markers, lipid profiles and cardiac tissue redox status were determined following RTSM treatment (250 and 500 mg/kg). Results As a result, RTSM treatment significantly mitigated ISO-triggered upregulation of cardiac-specific markers of injury creatine kinase and lactate dehydrogenase. RTSM treatment significantly attenuated ISO-induced increase in serum cholesterol and triglycerides as well alterations in serum lipoproteins. Determination of oxidative balance showed that RTSM treatment significantly blunted ISO-induced increase in malondialdehyde and decrease in nonprotein sulfhydryl in cardiac tissue. Six compounds were isolated and identified as gallocatechin1, taxifolin2, myricetin-3-O-β-glucoside3, catechin4, epicatechin5, and 3′, 8-binaringenin6 . Compound6 was isolated for the first time from the stem part ofRhus tripartita . Furthermore, RTSM treatment enhanced the survival fraction of cardiac cells exposed to oxidative stress in vitro. Conclusion We conclude that the antioxidant properties of RTSM treatment underpin its cardioprotective pharmacological effects, thus, providing biological evidence for the treatment of cardiovascular diseases usingRhus tripartita in indigenous medicine.